2009
DOI: 10.3141/2126-13
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Polymer-Modified Asphalt Mixture with Reclaimed Asphalt Pavement

Abstract: Reclaimed asphalt pavement (RAP) mixtures have shown good resistance to rutting for hot-mix asphalt (HMA) pavement. Mixtures with polymer-modified binders such as styrene-butadiene-styrene (SBS) have also shown good performance against rutting and cracking. This paper presents the laboratory evaluations used to determine the rutting and cracking performance of the RAP mixtures with SBS polymer-modified binders as virgin binders. The asphalt pavement analyzer (APA) test and indirect tensile (IDT) test were cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(23 citation statements)
references
References 10 publications
(7 reference statements)
2
13
0
3
Order By: Relevance
“…It can also note that the rut depth did not show a significant different between different amount of RAP material in mixtures without polymer-modified binder when compared with the mixture with polymer-modified binder. This agrees with the findings of (Kim et al 2009). It can be concluded that binder modified with SBS polymer makes the mixture stiffer than unmodified asphalt binder.…”
Section: Rutting Test Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It can also note that the rut depth did not show a significant different between different amount of RAP material in mixtures without polymer-modified binder when compared with the mixture with polymer-modified binder. This agrees with the findings of (Kim et al 2009). It can be concluded that binder modified with SBS polymer makes the mixture stiffer than unmodified asphalt binder.…”
Section: Rutting Test Resultssupporting
confidence: 93%
“…10, No. 3, July 2019 21 butadiene-styrene (SBS) have also shown a good performance against rutting and cracking (Kim et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Adding RAP materials improved the ITS values and reduced the moisture susceptibility of the mixture; however, adding CR to the mixture had a slightly negative impacts on the mixtures [13]. Kim S. et al in 2009 used Asphalt Pavement Analyzer (APA) and the Indirect Tensile Tests (IDT) to investigate the performance of rutting and cracking of SBS polymermodified asphalt mixture mixed with RAP. Different percentages of RAP were used, which were 0%, 15%, 25%, and 35%.…”
Section: Introductionmentioning
confidence: 99%
“…Different percentages of RAP were used, which were 0%, 15%, 25%, and 35%. Regardless of the amounts of RAP materials in HMA, the RAP mixtures with SBS modified binders worked well [18]. Reyes-Ortiz et al in 2012 evaluated the mechanical responses of dense-graded HMA mixtures after partial, and then total replacements of aggregates by recycled asphalt material and using asphalt binder grades of 60/70 and 80/100.…”
Section: Introductionmentioning
confidence: 99%
“…Este tipo de defeito se origina do acúmulo de deformações plásticas em uma ou mais camadas do pavimento (revestimento, base, sub-base e reforço de subleito) e no subleito. Em nível laboratorial, o estudo da deformação permanente em misturas asfálticas é geralmente feito por meio de simuladores de tráfego (D'Angelo et al, 2007;Kim et al, 2009;Moura, 2010;Reinke, 2010;FHWA, 2011;Wasage et al, 2011;Gibson et al, 2012) e de ensaios de fluência e recuperação, também chamados de flow number (Witczak et al, 2002;Nascimento, 2008;Wasage et al, 2009;Onofre, 2012;Onofre et al, 2013;Apeagyei, 2014). Outros métodos como o monitoramento de pistas experimentais (Moura, 2010) e o uso de ensaios triaxiais (Witczak et al, 2002;Borges, 2014) e de módulo dinâmico (Witczak et al, 2002;Li et al, 2011) também podem ser encontrados na literatura.…”
Section: Introductionunclassified